Elton John [videorecording (DVD)] (A&E Television Networks : Distributed by New Video, 2008)
See Sir Elton John behind the scenes and watch the legendary rock star prepare for his spectacular Red Piano show at Caesar's Palace. Gain an all-access pass to Elton's life and archives, including clips, music, performances, and home videos spanning his entire career to date.